2016
DOI: 10.1111/dom.12693
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term safety and efficacy of fasiglifam (TAK‐875), a G‐protein‐coupled receptor 40 agonist, as monotherapy and combination therapy in Japanese patients with type 2 diabetes: a 52‐week open‐label phase III study

Abstract: This multicentre, open-label, phase III study investigated the safety and efficacy of the G-protein-coupled receptor 40 agonist fasiglifam. Japanese patients with type 2 diabetes and inadequate glycaemic control despite diet and/or exercise (n = 282), or despite diet and/or exercise plus one oral antidiabetic agent [sulphonylurea (n = 262), rapid-acting insulin secretagogue (n = 124), α-glucosidase inhibitor (n = 141), biguanide (n = 136), thiazolidinedione (n = 139) or dipeptidyl peptidase-4 inhibitor (n = 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 10 publications
1
48
0
Order By: Relevance
“…AMG 009 also affects other hepatic transporters involved in the regulation of hepatic bile acids (e.g., MRP2 (stimulation, followed by inhibition, no IC 50 generated), MRP3 (1.1 μmol/L), and MRP4 (13.5 μmol/L)). Recent work with TAK‐875, an agent that caused clinical hepatotoxicity in a small number of patients at 50 mg once daily during a Phase 3 clinical study, also showed similar potencies across numerous hepatic transporters involved in bile acid transport . Unfortunately, none of these studies had clinical samples which could be used to interrogate the possible causal effect relationship between BSEP inhibition as a purported mechanism driving liver injury with evidence in affected subjects or patients.…”
Section: Discussionmentioning
confidence: 99%
“…AMG 009 also affects other hepatic transporters involved in the regulation of hepatic bile acids (e.g., MRP2 (stimulation, followed by inhibition, no IC 50 generated), MRP3 (1.1 μmol/L), and MRP4 (13.5 μmol/L)). Recent work with TAK‐875, an agent that caused clinical hepatotoxicity in a small number of patients at 50 mg once daily during a Phase 3 clinical study, also showed similar potencies across numerous hepatic transporters involved in bile acid transport . Unfortunately, none of these studies had clinical samples which could be used to interrogate the possible causal effect relationship between BSEP inhibition as a purported mechanism driving liver injury with evidence in affected subjects or patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, dogs had a TAK-875 plasma AUC 0 – 24 of 3800 μg*h/ml after 14 days of dosing at this concentration (Supplementary Table 4). Humans were administered TAK-875 (fasiglifam) at 25 and 50 mg in phase 3 clinical trials that were ultimately discontinued due to concerns about liver safety (Kaku et al , 2015, 2016). By comparison of exposures, the 600 mg/kg dogs had an exposure approximately 40- to 100-fold greater than humans who received repeat doses of 25 or 50 mg TAK-875 (AUC 0 – 24 of 40.3 and 100.3 μg*h/ml, respectively) (Leifke et al , 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical data indicated that there was a benefit for patients who received TAK-875 based on improved glycemic parameters (Kaku et al , 2013). However, the development activities of TAK-875 were voluntarily terminated in 2013 due to liver safety concerns (Kaku et al , 2015, 2016). This outcome presented an opportunity to investigate potential mechanisms of the toxicity with animal models.…”
mentioning
confidence: 99%
“…20 However, later studies did not persistently show the benefit of FFAR1 deficiency under chronic fatty acid loading in mouse models in vivo and in vitro. 23 A new generation of agonists with better safety profiles has been actively in development and may soon become a new class of therapeutic agents for T2D. 11 In humans, FFAR1 is not among the T2D risk loci in genome-wide association study (GWAS), and nonsynonymous variants of FFAR1 have not shown correlation with the development of T2D.…”
Section: How Do Fa and Lipid Metabolites Support Gsis?mentioning
confidence: 99%